2020
DOI: 10.1186/s13619-020-00045-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-derived mesenchymal stem cells and chitosan/poly (vinyl alcohol) nanofibrous scaffolds for cartilage tissue engineering

Abstract: Osteoarthritis (OA) has been defined as a chronic inflammatory joint disease characterized by progressive articular cartilage degeneration. Recently growing interest in regenerative medicine, using cell therapy and tissue engineering, where cellular components in combination with engineered scaffolds and bioactive materials were used to induce functional tissue regeneration. In the present study, nanofibrous scaffold based on chitosan (CS)/poly (vinyl alcohol) (PVA) were used to develop biologically functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Although adding dECM causes the scaffolds to lose more weight, the presence of dECM makes these scaffolds suitable for special treatments in which long-term presence of membrane is not favorable such as PDL reconstructions. Opposite to present study, In a study by Jie Xu et al which shown the degradation rate of dECM/Gelatin/Chitosan scaffold was too much faster than PVA/Chitosan with dECM scaffolds [29].…”
Section: Discussionmentioning
confidence: 50%
“…Although adding dECM causes the scaffolds to lose more weight, the presence of dECM makes these scaffolds suitable for special treatments in which long-term presence of membrane is not favorable such as PDL reconstructions. Opposite to present study, In a study by Jie Xu et al which shown the degradation rate of dECM/Gelatin/Chitosan scaffold was too much faster than PVA/Chitosan with dECM scaffolds [29].…”
Section: Discussionmentioning
confidence: 50%
“…The MBs may contain residues of PVA molecules. PVA is a biodegradable and biocompatible polymer and has been studied in various medical applications such as tissue engineering, drug delivery, and as a major component of the MB shell . Therefore, its presence in the final product should not impair the biocompatibility of the PLGA MBs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Bone MSCs promote tissue repair through paracrine under specific environments. Chitosan/polyvinyl alcohol nanofiber scaffolds (CS/PVA scaffolds) can be used to simulate the extracellular matrix and facilitate the proliferation and differentiation of human adipose tissue-derived mesenchymal stem cells into chondrocytes ( Nour-Eldeen et al, 2020 ).…”
Section: Osteocartilage Regeneration Scaffoldmentioning
confidence: 99%